2011
DOI: 10.5505/tjtes.2011.53333
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects of spinal immobilization devices on pulmonary function in healthy volunteer individuals

Abstract: AMAÇSpinal immobilizasyon cihazlarının solunum fonksiyonları üzerindeki etkileri araştırıldı. GEREÇ VE YÖNTEMBu çalışma, sağlıklı gönüllü kişilerde yapılan kesitsel bir çalışmadır, 60 gönüllü dahil edildi. Yatar pozisyondayken tam spirometre uygulandı ve tüm deneklerde zorlu vital kapasite (FVC), zorlu birinci saniye ekspiratuvar hacim (FEV1) ve FEV1/FVC kaydedildi. Sonra, Philadelphia tipi boyunluk (Philly) ve travma yeleği (Kendrick extrication device=KED) tüm deneklere uygulandı. Boyunluk ve KED uygulamasın… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 11 publications
0
25
0
1
Order By: Relevance
“…Additionally, these devices have been shown to directly compromise respiration. Ay et al 20 demonstrated statistically significant decreases in forced expiratory volume in 1 second (FEV 1 ) and forced vital capacity with both the KED and long spinal backboard. Another study showed a 15% decrease in FEV 1 with a cervical collar and backboard, and noted that respiratory restriction was more pronounced with age.…”
Section: Effectiveness Of the Cervical Collar In Immobilization Of Thmentioning
confidence: 99%
“…Additionally, these devices have been shown to directly compromise respiration. Ay et al 20 demonstrated statistically significant decreases in forced expiratory volume in 1 second (FEV 1 ) and forced vital capacity with both the KED and long spinal backboard. Another study showed a 15% decrease in FEV 1 with a cervical collar and backboard, and noted that respiratory restriction was more pronounced with age.…”
Section: Effectiveness Of the Cervical Collar In Immobilization Of Thmentioning
confidence: 99%
“…There have been several studies on the effects of spinal immobilization on pulmonary function, and these studies have shown that forced expiratory volume in 1 s (FEV 1 ) and forced vital capacity (FVC) levels significantly decreased at the 5 th and 30 th minutes (18)(19)(20). In our study, secondary indicators of pulmonary function, breath rate, and oxygen saturation were also assessed, and it was shown that they were not affected by spinal immobilization.…”
Section: Discussionmentioning
confidence: 98%
“…In a study performed by Ay et al, which used spirometry to analyze the effect of neck spine immobilization on pulmonary function in healthy individuals, the authors suggested that the use of a neck collar would cause a significant decrease in spirometry parameters in patients (13). In another study, Bauer et al evaluated the effect of neck collar fixation on spirometry parameters and stated that using a neck collar caused a significant decrease in the rate of FVC, FEV1 and FEF25 - 75 (14).…”
Section: Discussionmentioning
confidence: 99%